Preparation method of super-wear-resistant and super-hydrophobic surface and super-wear-resistant and super-hydrophobic surface
By coating low-surface energy polymers on the surface of the metal substrate and forming a concave-convex grating hydrophobic array using laser etching, the existing superhydrophobic surface preparation methods and poor wear resistance are solved, and superhydrophobic surfaces with high wear resistance and short preparation periods are achieved.
Patent Information
- Application Number
- CN202411642304.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-03-11
AI Technical Summary
The existing superhydrophobic surface preparation methods are complex, have poor wear resistance and short service life.
A low-surface energy polymer is used to coat the surface of the metal substrate, and a concave-convex grating hydrophobic array is formed by laser etching. Combined with a low-surface energy polymer with a mass ratio of 5 to 20:10:1 of micron-scale Cr powder, PDMS prepolymer and PDMS curing agent, a low-surface energy polymer with a mass ratio of 5 to 20:10:1, to form mixed metal protrusions to improve wear resistance.
It significantly reduces the preparation cycle, improves the wear resistance and service life of the superhydrophobic surface, and solves the problems of cumbersome preparation and poor wear resistance in traditional methods.
Smart Images

Figure CN119588593A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of material surface treatment, and particularly relates to a preparation method of a super wear-resistant and super hydrophobic surface and the super wear-resistant and super hydrophobic surface. Background Art
[0002] A super-hydrophobic surface refers to a surface with a water contact angle WCA greater than 150° and a rolling angle WSA less than 10°. Super-hydrophobic surfaces are widely used in various industries and daily life because of their excellent self-cleaning, anti-fouling and anti-corrosion properties.
[0003] The traditional method of preparing super-hydrophobic surfaces is to prepare micro-nano structures on the surface of metal substrates by acid-base corrosion or electrospinning, and then chemically modify the surface of the metal substrate with micro-nano structures to achieve low surface energy, thereby obtaining a super-hydrophobic surface. The traditional method of preparing super-hydrophobic surfaces is complicated in the preparation process of micro-nano structures and has a long preparation cycle. In addition, the super-hydrophobic surface after chemical modification has poor mechanical durability and is easily exposed to substances in the external environment and loses its super-hydrophobic effect. It is easily affected by the outside world and has a short service life. Summary of the invention
[0004] The purpose of the present invention is to overcome the defects of the prior art that the super-hydrophobic surface preparation process is complicated, the wear resistance is poor, and the service life is short, and to provide a method for preparing a super-wear-resistant super-hydrophobic surface and a super-wear-resistant super-hydrophobic surface which greatly reduces the preparation cycle and has super-wear-resistant performance.
[0005] The technical solution adopted by the present invention to solve its technical problem is:
[0006] A method for preparing a super wear-resistant and super hydrophobic surface comprises the following steps:
[0007] Step 1: Pre-treat the metal substrate;
[0008] Step 2: preparing a low surface energy polymer, wherein the low surface energy polymer comprises micron-sized Cr powder, PDMS prepolymer, and PDMS curing agent, wherein the mass ratio of the micron-sized Cr powder, PDMS prepolymer, and PDMS curing agent is 5 to 20:10:1;
[0009] Step 3: uniformly coating the low surface energy polymer prepared in step 2 on the surface of the metal substrate pretreated in step 1, and curing the surface of the metal substrate to form a solid coating layer;
[0010] Step 4: laser etching the surface of the metal substrate with the solid coating layer to form a concave-convex grating hydrophobic array;
[0011] Step 5: Post-treat the metal substrate with the concave-convex grating hydrophobic array in step 4 to obtain a super wear-resistant super hydrophobic surface.
[0012] Specifically, the method for preparing the low surface energy polymer in step 2 comprises the following steps:
[0013] Weigh the mass ratio of micron-sized Cr powder, PDMS, and PDMS curing agent to be 5-20:10:1;
[0014] The PDMS and the PDMS curing agent are mixed to prepare a PDMS solution by ultrasonic stirring;
[0015] Micron-sized Cr powder is added into the prepared PDMS solution and fully distributed at a temperature of 20° C. to 40° C. to obtain a low surface energy polymer.
[0016] Specifically, in the step 4, an infrared laser device is used to laser etch the surface of the metal substrate with a solid coating layer. The processing speed of the infrared laser device is 50 mm / s to 200 mm / s, the pulse frequency is 20 kHz to 200 kHz, the processing times is 10 to 20 times, the processing spacing is 100 μm to 300 μm, and the processing power is 20 W to 30 W.
[0017] Specifically, the formation of the concave-convex grating hydrophobic array in step 4 includes the following processes:
[0018] The surface of the metal substrate with the solid coating layer is laser-etched by using an infrared laser device. The laser etching melts the surface of the metal substrate at high temperature into small metal droplets, and the molten part of the metal substrate forms a hydrophobic groove.
[0019] The molten metal droplets are mixed with the melted solid coating layer on the surface of the metal substrate and gathered at the edge of the laser-etched groove to form mixed metal hydrophobic protrusions.
[0020] Specifically, the curing treatment in step three is as follows: placing the metal substrate coated with the low surface energy polymer in a blast drying oven, heating and drying for curing; the curing temperature of the heating and drying curing is 70° to 90°; and the curing time is 2 to 3 hours.
[0021] Specifically, the mass ratio of micron-sized Cr powder, PDMS prepolymer, and PDMS curing agent in the low surface energy polymer is 10:10:1;
[0022] Specifically, the particle size of the micron-sized Cr powder is 1 μm to 6 μm.
[0023] Specifically, the pretreatment of the metal substrate in step 1 includes the following steps:
[0024] A1. Grind the metal substrate, i.e. use sandpaper to remove the oxide on the surface of the metal substrate;
[0025] A2. Ultrasonic cleaning of the polished metal substrate, that is, placing the polished metal substrate into anhydrous ethanol for ultrasonic cleaning;
[0026] A3. Drying the cleaned metal substrate in step A2, that is, placing the cleaned metal substrate in a blast drying oven to dry.
[0027] Specifically, the post-processing described in step 5 includes the following steps:
[0028] B1. The metal substrate having the concave-convex grating hydrophobic array formed in step 4 is placed in a solvent or a cleaning agent for ultrasonic cleaning; the ultrasonic cleaning time is 10 min to 20 min;
[0029] B2. Place the metal substrate cleaned in step B1 into a forced air drying oven and dry it at room temperature.
[0030] A super wear-resistant and super hydrophobic surface is prepared by the above-mentioned method for preparing the super wear-resistant and super hydrophobic surface.
[0031] The beneficial effects of the method for preparing a super wear-resistant and super hydrophobic surface of the present invention are:
[0032] The preparation method of the super-wear-resistant super-hydrophobic surface and the super-wear-resistant super-hydrophobic surface of the present invention abandon the traditional preparation process of first performing micro-nano structure treatment on a metal substrate and then performing low surface energy treatment. A low surface energy polymer is first coated on the surface of the metal substrate, and then a concave-convex grating hydrophobic array is etched on the surface of the metal substrate coated with the low surface energy polymer by laser etching. The low surface energy polymer is melted and then put into the metal substrate for mixing and aggregation on the surface of the metal substrate to form a concave-convex grating hydrophobic array, which not only eliminates the cumbersome process of micro-nano structure treatment and reduces the cumbersomeness of preparing the super-hydrophobic surface, but also the setting of the low surface energy and the concave-convex grating hydrophobic array are simultaneously performed during laser etching, which can ensure the hydrophobic performance of the super-hydrophobic surface and greatly save the preparation cycle, thereby solving the problem of cumbersome super-hydrophobic surface preparation method and long cycle in the prior art.
[0033] The low surface energy polymer in the present invention is prepared by mixing micron-grade Cr powder, PDMS prepolymer and PDMS curing agent in a mass ratio of 5 to 20:10:1. During laser etching, the mixed metal protrusions formed by mixing the molten metal substrate and the Cr material in the low surface energy polymer have strong super wear resistance, so as to solve the problem of poor mechanical resistance of the super hydrophobic surface obtained by the traditional super wear-resistant super hydrophobic surface preparation method in the prior art. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.
[0035] Figure 1 It is a preparation method of a super wear-resistant and super hydrophobic surface and a flow chart of a super wear-resistant and super hydrophobic surface according to an embodiment of the present invention.
[0036] Figure 2 1 is a flow chart of the steps of pre-treating a metal substrate in an embodiment of the present invention.
[0037] Figure 3 3 is a scanning electron microscope image of the super-hydrophobic surface prepared in Example 1 of the present invention.
[0038] Figure 4 3 is a contact angle diagram of the super-hydrophobic surface prepared in Example 1 of the present invention.
[0039] Figure 5 It is a schematic diagram of the friction of the super-hydrophobic surface prepared in Example 1 of the present invention.
[0040] Figure 6 This is a scanning electron microscope image of the super-hydrophobic surface prepared in Example 1 of the present invention after friction and wear.
[0041] Figure 7 This is a contact angle diagram of the super-hydrophobic surface prepared in Example 1 of the present invention after friction and wear.
[0042] Figure 8 3 is a scanning electron microscope image of the super-hydrophobic surface prepared in Example 2 of the present invention.
[0043] Fig. 9 3 is a contact angle diagram of the super-hydrophobic surface prepared in Example 2 of the present invention.
[0044] Fig.10 This is a scanning electron microscope image of the super-hydrophobic surface prepared in Example 2 of the present invention after friction and wear.
[0045] Fig.11 This is a contact angle diagram of the super-hydrophobic surface prepared in Example 2 of the present invention after friction and wear.
[0046] Fig.12 It is a scanning electron microscope image of the super hydrophobic surface prepared in comparative example.
[0047] Fig.13 It is the contact angle diagram of the super hydrophobic surface prepared in comparative example.
[0048] Fig.14 It is a scanning electron microscope image of the super hydrophobic surface prepared in comparative example after friction and wear.
[0049] Fig.15 It is a contact angle diagram of the super hydrophobic surface prepared in comparative example after friction and wear. DETAILED DESCRIPTION
[0050] The present invention will now be described in further detail with reference to the accompanying drawings. These drawings are simplified schematic diagrams, which only illustrate the basic structure of the present invention in a schematic manner, and therefore only show the components related to the present invention.
[0051] like Figure 1 The method for preparing a super wear-resistant and super hydrophobic surface and a specific embodiment of the super wear-resistant and super hydrophobic surface of the present invention shown include the following steps:
[0052] Step 1: Pre-treat the metal substrate;
[0053] Step 2: preparing a low surface energy polymer, wherein the low surface energy polymer comprises micron-sized Cr powder, PDMS, and a PDMS curing agent, wherein the mass ratio of the micron-sized Cr powder, the PDMS prepolymer, and the PDMS curing agent is 5 to 20:10:1;
[0054] Step 3: uniformly coating the low surface energy polymer prepared in step 2 on the surface of the metal substrate pretreated in step 1, and curing the surface of the metal substrate to form a solid coating layer;
[0055] Step 4: laser etching the surface of the metal substrate with the solid coating layer to form a concave-convex grating hydrophobic array;
[0056] Step 5: Post-treat the metal substrate with the concave-convex grating hydrophobic array in step 4 to obtain a wear-resistant super-hydrophobic surface.
[0057] The preparation method of the super-wear-resistant super-hydrophobic surface and the super-wear-resistant super-hydrophobic surface in the present embodiment abandon the traditional preparation process of first performing micro-nano structure treatment on the metal substrate and then performing low surface energy treatment. A low surface energy polymer is first coated on the surface of the metal substrate, and then a concave-convex grating hydrophobic array is etched on the surface of the metal substrate coated with the low surface energy polymer by laser etching. The low surface energy polymer and the melted metal substrate are mixed and aggregated on the surface of the metal substrate to form a concave-convex grating hydrophobic array by laser etching. This not only eliminates the cumbersome process of micro-nano structure treatment and reduces the cumbersomeness of preparing the super-hydrophobic surface, but also simultaneously performs the setting of low surface energy and the concave-convex grating hydrophobic array during laser etching, which can not only ensure the hydrophobic performance of the super-hydrophobic surface, but also greatly save the preparation cycle, thereby solving the problem of cumbersome super-hydrophobic surface preparation method and long cycle in the prior art.
[0058] The details are as follows: Figure 2 As shown, the pretreatment of the metal substrate in step 1 of this embodiment includes the following steps:
[0059] A1. Grind the metal substrate, i.e. use sandpaper to remove the oxide on the surface of the metal substrate;
[0060] A2. Ultrasonic cleaning of the polished metal substrate, that is, placing the polished metal substrate into a solvent or cleaning agent for ultrasonic cleaning; wherein the solvent or cleaning agent is deionized water, anhydrous ethanol
[0061] A3. Drying the cleaned metal substrate in step A2, that is, placing the cleaned metal substrate in a blast drying oven to dry.
[0062] It is further explained that the low surface energy polymer in this embodiment is prepared by mixing micron-sized Cr powder, PDMS prepolymer, and PDMS curing agent in a mass ratio of 5 to 20:10:1. Specifically, the preparation method of the low surface energy polymer includes the following steps: weighing micron-sized Cr powder, PDMS prepolymer, and PDMS curing agent in a mass ratio of 5 to 20:10:1; mixing the PDMS prepolymer and the PDMS curing agent, and preparing a PDMS solution by ultrasonic stirring; adding micron-sized Cr powder to the prepared PDMS solution, and fully distributing it at a temperature of 20°C to 40°C to obtain a low surface energy polymer. Wherein, the particle size of the micron-sized Cr powder is 1μm to 6μm.
[0063] During laser etching, the mixed metal protrusions formed by the mixture of the molten metal substrate and the Cr material in the low surface energy polymer have strong wear resistance, so as to solve the problem of poor mechanical resistance of the super-hydrophobic surface obtained by the traditional super-wear-resistant super-hydrophobic surface preparation method in the prior art.
[0064] As a preferred embodiment, the curing treatment in step 3 is specifically as follows: placing the metal substrate coated with the low surface energy polymer in a blast drying oven, and drying and curing at room temperature or by heating. Specifically, the curing temperature of the heating drying curing is 70° to 90°; the curing time is 2 to 3 hours. The higher the temperature, the shorter the curing time, and corresponding adjustments can be made as needed.
[0065] In the step 4, the surface of the metal substrate with a solid coating layer is laser-etched by an infrared laser device, and the processing speed of the infrared laser device is 50 mm / s to 200 mm / s, the pulse frequency is 20 kHz to 200 kHz, the number of processing times is 10 to 20 times, the processing spacing is 100 μm to 300 μm, and the processing power is 20 W to 30 W. Wherein, the formation of the concave-convex grating hydrophobic array in step 4 includes the following process: the surface of the metal substrate with a solid coating layer is laser-etched by an infrared laser device, and the laser etching melts the surface of the metal substrate into small metal droplets at high temperature, and the molten part of the metal substrate forms a hydrophobic groove, and the small metal droplets formed by melting and the melted solid coating layer on the surface of the metal substrate are mixed and gathered at the edge of the laser-etched groove to form a mixed metal hydrophobic protrusion.
[0066] Laser etching is used to mix the low surface energy polymer with the melted metal substrate and aggregate it on the surface of the metal substrate to form a concave-convex grating hydrophobic array. During laser etching, the mixed metal protrusions formed by the mixture of the melted metal substrate and the Cr material in the low surface energy polymer have strong wear resistance. The use of Cr powder to enhance the wear resistance of the super hydrophobic surface of the metal substrate can be widely used in self-cleaning coatings, anti-fouling and waterproof protection, anti-corrosion materials, aerospace, transportation and other fields.
[0067] Finally, the laser-etched metal substrate is placed in a solvent or a cleaning agent for ultrasonic cleaning to remove the flying chips and slag generated by the laser processing. After being taken out, it is placed in a blast drying oven for drying to complete the preparation of the wear-resistant super-hydrophobic surface.
[0068] Embodiment 1
[0069] The metal substrate is made of copper alloy. The prepared copper plate is polished to remove surface oxides, placed in anhydrous ethanol for ultrasonic cleaning for 10 minutes to remove surface dirt and dust, and then taken out and placed in a forced air drying oven for drying.
[0070] Prepare low surface energy polymer, select micron-sized Cr powder, mix Cr powder, PDMS, and PDMS curing agent in a mass ratio of 10:10:1, and stir them evenly with a magnetic stirrer. The prepared low surface energy polymer is evenly coated on the surface of the pretreated copper plate, and the coated copper plate is placed in a blast drying oven for heating and drying, and the heating temperature is 80 degrees until the low surface energy polymer is solidified on the surface of the copper plate. The copper plate solidified with the low surface energy polymer is fixed on the infrared nanosecond laser stage, and the processing parameters of the infrared laser are set, including a processing speed of 200 mm / s, a pulse frequency of 150 kHz, 10 processing times, a processing spacing of 100 μmm, and a processing power of 20 W. After defining the processing parameters, the copper plate surface is subjected to regular grating array processing. After processing, use appropriate anhydrous ethanol and ultrasonically clean the laser-processed sample to remove the surface slag. Finally, the cleaned sample is placed in a blast drying oven for drying to remove surface moisture and obtain a superhydrophobic surface.
[0071] Figure 3 and Figure 4 They are respectively the scanning electron microscope image and the contact angle image of the super hydrophobic surface obtained in Example 1. Figure 5 As shown, 400-grit sandpaper is selected as the bottom surface, a weight of 100g is selected as the load, a single friction length is 10cm, 200 reciprocating friction cycles, and a total friction length of 20m. The test results are as follows Figure 4 The static water contact angle of the prepared wear-resistant super-hydrophobic surface is 156.2°, and the static water contact angle of the surface after friction and wear with 400-grit sandpaper is 150.4°. Figure 7 .like Figure 3and Figure 6 From the comparison before and after friction and wear, it can be seen that the wear degree of the super-wear-resistant and super-hydrophobic surface of the first embodiment is relatively light, and still meets the super-hydrophobic requirements.
[0072] Embodiment 2
[0073] The metal substrate is made of copper alloy. The prepared copper plate is polished to remove surface oxides, placed in anhydrous ethanol for ultrasonic cleaning for 15 minutes to remove surface dirt and dust, and then taken out and placed in a forced air drying oven for drying.
[0074] Prepare low surface energy polymer, select micron-sized Cr powder, mix Cr powder, PDMS, and PDMS curing agent in a mass ratio of 5:10:1, and stir them evenly with a magnetic stirrer. The prepared low surface energy polymer is evenly coated on the surface of the pretreated copper plate, and the coated copper plate is placed in a blast drying oven for heating and drying, and the heating temperature is 90 degrees until the low surface energy polymer is solidified on the surface of the copper plate. The copper plate solidified with the low surface energy polymer is fixed on the infrared nanosecond laser stage, and the processing parameters of the infrared laser are set, including a processing speed of 100 mm / s, a pulse frequency of 20 kHz, 20 processing times, a processing spacing of 300 μmm, and a processing power of 30 W. After defining the processing parameters, the copper plate surface is subjected to regular grating array processing. After processing, use appropriate anhydrous ethanol and ultrasonically clean the sample processed by the laser to remove the surface slag. Finally, the cleaned sample is placed in a blast drying oven for drying to remove surface moisture and obtain a superhydrophobic surface.
[0075] Figure 8 and Fig. 9 They are the SEM image and contact angle image of the super hydrophobic surface obtained in Example 2. The 400-grit sandpaper is still used as the bottom surface, the weight of 100g is selected as the load, the single friction length is 10cm, the reciprocating friction is 200 cycles, and the total friction length is 20m. The test results are as follows Figure 8 The static water contact angle of the prepared wear-resistant super-hydrophobic surface is 154.4°, and the static water contact angle of the surface after friction and wear with 400-grit sandpaper is 150.6°. Fig.11 , still meeting the super-hydrophobic requirements, Figure 8 and Fig.10 From the comparison before and after friction and wear, it can be seen that the wear degree of the super wear-resistant and super hydrophobic surface of the second embodiment is relatively light.
[0076] Comparative Example
[0077] like Fig.12As shown in FIG. 1 , the comparative example is a super-hydrophobic surface prepared by the prior art, and the 400-mesh sandpaper is also selected as the bottom surface, a weight of 100 g is selected as the load, a single friction length is 10 cm, 200 reciprocating friction cycles, and a total friction length of 20 m. Fig.13 The contact angle diagram of the super hydrophobic surface prepared by the prior art in the comparative example before friction is 156.7°. Fig.14 The scanning electron microscope images are the same as those of the first and second embodiments after the friction requirements. Fig.12 The comparison clearly shows that the hydrophobic protrusions are severely worn. Fig.15 This is a contact angle diagram of the comparative super-hydrophobic surface after friction and wear operation, and its contact angle is 140.5°, which does not meet the super-hydrophobicity requirement.
[0078] It can be seen from Example 1, Example 2 and the comparative example that the wear resistance of the super-hydrophobic surface prepared by the preparation method of the present invention is significantly better than that of the prior art. While having super-hydrophobic properties, it has excellent wear resistance, and is simple to operate, easy to control the steps, short preparation cycle, suitable for large-scale production, prepared using common materials, low cost, and no environmental pollution.
[0079] It should be understood that the specific embodiments described above are only used to explain the present invention, and are not used to limit the present invention. Obvious changes or modifications derived from the spirit of the present invention are still within the protection scope of the present invention.
Claims
1. A method for preparing a super wear-resistant and super hydrophobic surface, characterized in that: The following steps are involved: Step 1: Pre-treat the metal substrate; Step 2: preparing a low surface energy polymer, wherein the low surface energy polymer comprises micron-sized Cr powder, PDMS prepolymer, and PDMS curing agent, wherein the mass ratio of the micron-sized Cr powder, PDMS prepolymer, and PDMS curing agent is 5 to 20:10:1; Step 3: uniformly coating the low surface energy polymer prepared in step 2 on the surface of the metal substrate pretreated in step 1, and curing the surface of the metal substrate to form a solid coating layer; Step 4: laser etching the surface of the metal substrate with the solid coating layer to form a concave-convex grating hydrophobic array; Step 5: Post-treat the metal substrate with the concave-convex grating hydrophobic array in step 4 to obtain a super wear-resistant super hydrophobic surface.
2. A method for preparing a super wear-resistant super hydrophobic surface according to claim 1, characterized in that, The method for preparing the low surface energy polymer in step 2 comprises the following steps: Weigh the mass ratio of micron-sized Cr powder, PDMS, and PDMS curing agent to be 5-20:10:1; The PDMS and the PDMS curing agent are mixed to prepare a PDMS solution by ultrasonic stirring; Micron-sized Cr powder is added into the prepared PDMS solution and fully distributed at a temperature of 20° C. to 40° C. to obtain a low surface energy polymer.
3. A method for preparing a super wear-resistant super hydrophobic surface according to claim 1, characterized in that: In the step 4, an infrared laser device is used to laser etch the surface of the metal substrate with a solid coating layer. The processing speed of the infrared laser device is 50 mm / s to 200 mm / s, the pulse frequency is 20 kHz to 200 kHz, the processing times is 10 to 20 times, the processing spacing is 100 μm to 300 μm, and the processing power is 20 W to 30 W.
4. A method for preparing a super wear-resistant super hydrophobic surface according to claim 3, characterized in that, Step 4 forms a concave-convex grating hydrophobic array The process includes: The surface of the metal substrate with the solid coating layer is laser-etched by using an infrared laser device. The laser etching melts the surface of the metal substrate at high temperature into small metal droplets, and the molten part of the metal substrate forms a hydrophobic groove. The molten metal droplets are mixed with the melted solid coating layer on the surface of the metal substrate and gathered at the edge of the laser-etched groove to form mixed metal hydrophobic protrusions.
5. A method for preparing a super wear-resistant super hydrophobic surface according to claim 1, characterized in that, The curing treatment in step three is specifically as follows: placing the metal substrate coated with the low surface energy polymer in a blast drying oven, heating and drying for curing; the curing temperature of the heating and drying curing is 70° to 90°; and the curing time is 2 to 3 hours.
6. The method for preparing a super wear-resistant super hydrophobic surface according to claim 1, characterized in that: The mass ratio of the micron-sized Cr powder, the PDMS prepolymer and the PDMS curing agent in the low surface energy polymer is 10:10:
1.
7. A method for preparing a super wear-resistant super hydrophobic surface according to claim 6, characterized in that: The particle size of the micron-sized Cr powder is 1 μm to 6 μm.
8. The method for preparing a super wear-resistant super hydrophobic surface according to claim 1, characterized in that: The pretreatment of the metal substrate in step 1 includes the following steps: A1. Grind the metal substrate, i.e. use sandpaper to remove the oxide on the surface of the metal substrate; A2. Ultrasonic cleaning of the polished metal substrate, that is, placing the polished metal substrate into anhydrous ethanol for ultrasonic cleaning; A3. Drying the cleaned metal substrate in step A2, that is, placing the cleaned metal substrate in a blast drying oven to dry.
9. A method for preparing a super wear-resistant super hydrophobic surface according to claim 1, characterized in that, The post-processing described in step 5 includes the following steps: B1. The metal substrate having the concave-convex grating hydrophobic array formed in step 4 is placed in a solvent or a cleaning agent for ultrasonic cleaning; the ultrasonic cleaning time is 10 min to 20 min; B2. Place the metal substrate cleaned in step B1 into a forced air drying oven and dry it at room temperature.
10. A super wear-resistant and super hydrophobic surface, characterized in that: The super wear-resistant and super hydrophobic surface is prepared by the preparation method of any one of claims 1 to 9.